2009
DOI: 10.1007/s10344-009-0331-y
|View full text |Cite
|
Sign up to set email alerts
|

Foraging habitats of Myotis emarginatus in Central Europe

Abstract: We radio-tracked Myotis emarginatus in Upper Bavaria, Germany to identify the key-foraging habitats and to enable an adequate habitat management for this endangered species. The studied females foraged at a distance of up to 8.1 km around their colony roost. The average distance of the foraging area was 3.7 km, where 70% of foraging areas were located within a distance of 5 km and 90% within 6 km of the nurseries. Moreover, these bats spent about 75% of their foraging time within 5 km and 85% within a 6-km rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
3
14
0
3
Order By: Relevance
“…Consistent with the results obtained in other European studies, R. ferrumequinum and M. emarginatus were strongly dependent on the availability of deciduous woodland and riparian vegetation within a 5 km-distance of their maternity roost (Flaquer et al, 2008;Flanders and Jones, 2009;Zahn et al, 2010). This dependence on deciduous woodland and riparian vegetation is perhaps even more important in our case study because these habitats are rare in our study area.…”
Section: Bats and Foraging Habitat Selectionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the results obtained in other European studies, R. ferrumequinum and M. emarginatus were strongly dependent on the availability of deciduous woodland and riparian vegetation within a 5 km-distance of their maternity roost (Flaquer et al, 2008;Flanders and Jones, 2009;Zahn et al, 2010). This dependence on deciduous woodland and riparian vegetation is perhaps even more important in our case study because these habitats are rare in our study area.…”
Section: Bats and Foraging Habitat Selectionsupporting
confidence: 93%
“…This data is usually obtained through radio-tracking surveys (e.g. Flaquer et al, 2008;Zahn et al, 2010;Razgour et al, 2011), which are often intrusive for species and require significant financial investment and logistic organization. However, Bellamy et al (2013) showed that at a local scale, HSMs can also be built with data obtained by acoustic surveys.…”
Section: Speciesmentioning
confidence: 99%
“…Associative learning of cues that indirectly indicate the presence of prey, and the flexibility to update these associations rapidly over time, should thus be more important in these bats than in the former two groups. As a representative of this group, we investigated M. emarginatus , a clutter specialist sympatric with the other two species in our study [41][44].…”
Section: Introductionmentioning
confidence: 99%
“…La ausencia de otros refugios alternativos en los alrededores, probablemente ha impulsado a las colonias a ocupar estas casetas. Además puede ser determinante el hecho de que las casetas se sitúen en un lugar tranquilo, junto a un río bien conservado, con bosque de ribera que atraviesa un gran encinar y un pinar, lo cual constituye un hábitat muy adecuado para la cría de estas especies (Roué & Barataud 1999, Flaquer et al 2008, Zahn et al 2010). …”
Section: Discussionunclassified